Coxitis in early axial spondyloarthritis - E. M. Agafonova; T. V. Dubinina; D. G. Rumyantseva; A. B. Demina; A. V. Smirnov; Sh. Erdes (Современная ревматология, 2019)
In Russia, coxitis is one of the most common extra-axial manifestations of ankylosing spondylitis (AS). However, many issues regarding its early diagnosis remain unresolved.Objective: to compare the clinical manifestations of coxitis with the data from an instrumental examination of CoRSAR cohort (Cohort of Early Axial Spondyloarthritis) patients.Patients and methods. Examinations were made in 175 patients (mean age, 28.2±5.7 years) diagnosed as having axial spondyloarthritis (axSpA) with inflammatory back pain lasting up to 5 years, which occurred at the age of ≤45 years. There was non-radiographic axSpA (nraxSpA) in 69 patients and AS in 106 patients. 87% of patients were HLA-B27-positive. The median disease duration was 23.8 [1–60] months; BASDAI was 3.3±1.94. Regardless of complaints, all the patients underwent hip X-ray and ultrasound studies and 54 more patients had magnetic resonance imaging (MRI).Results and discussion. The clinical signs of coxitis were present in 95 (54%) patients, of them 60% were diagnosed with AS and 40% had nraxSpA. According to the numerical pain rating scale (NPRS), the median hip joint pain was 4 [3; 7]. Limited joint movement was observed in 6 (3.4%) patients. The level of hip joint pain correlated with BASDAI (r=0.53) and ASDAS (r=0.30). The ultrasound signs of coxitis were detected in 42 (24%) patients; of them 26 (62%) had the clinical manifestations of hip joint injury, and such changes were absent in 16 patients. The patients with ultrasound signs of coxitis were noted to have a higher disease activity; peripheral arthritis and enthesitis were more common. According to MRI, coxitis was diagnosed in 39 (72%) of the 54 examinees, while the disease was asymptomatic in 10%.Conclusion. Different diagnostic methods used in patients with early axSpA could reveal coxitis in 33% of cases. The patients with coxitis show higher laboratory disease activity than those without hip joint injury. It is necessary to include MRI and ultrasound in the mandatory examination of patients with axSpA.